On the Spatial Distribution of Minor Species in Jupiter's Troposphere as Inferred From Juno JIRAM Data. Issue 4 (26th March 2020) - Grassi, D.; Adriani, A.; Mura, A.; Atreya, S. K.; Fletcher, L. N.; Lunine, J. I.; Orton, G. S.; Bolton, S.; Plainaki, C.; Sindoni, G.; Altieri, F.; Cicchetti, A.; et al.
Abstract: The spatial distribution of water, ammonia, phosphine, germane, and arsine in the Jupiter's troposphere has been inferred from the Jovian Infrared Auroral Mapper (JIRAM) Juno data. Measurements allow us to retrieve the vertically averaged concentration of gases between ~3 and 5 bars from infrared‐bright spectra. Results were used to create latitudinal profiles. The water vapor relative humidity varies with latitude from <1% to over 15%. At intermediate latitudes (30–70°) the water vapor maxima are associated with the location of cyclonic belts, as inferred from mean zonal wind profiles (Porco et al., 2003). The high‐latitude regions (beyond 60°) are drier in the north (mean relative humidity around 2–3%) than the south, where humidity reaches 15% around the pole. The ammonia volume mixing ratio varies from 1 × 10 −4 to 4 × 10 −4 . A marked minimum exists around 10°N, while data suggest an increase over the equator. The high‐latitude regions are different in the two hemispheres, with a gradual increase in the south and more constant values with latitude in the north. The phosphine volume mixing ratio varies from 4 × 10 −7 to 10 × 10 −7 . A marked minimum exists in the North Equatorial Belt. For latitudes poleward 30°S and 30°N, the northern hemisphere appears richer in phosphine, with a decrease toward the pole, while the opposite is observed in the south. JIRAM data indicate an increase of germane volume mixing ratio from 2 × 10 −10 to 8 × 10 −10 from both poles to 15°S, with a depletion centered around the equator. Arsine presents the opposite trend, with maximum values of 6 × 10 −10 at the two poles and minima below 1 × 10 −10 around 20°S. Key Points: Horizontal variations of gases are dominated by latitudinal components; longitudinal variations are relatively more important for water Phosphine and germane abundances fit well the model of disequilibrium species transported upward from deep troposphere by vertical mixing Strong upturn of arsine at polar latitudes seen by JIRAM cannot be explained by the diffusion‐kinetics model